Pelatihan Penggunaan Aplikasi Mendeley dan Turnitin Guna Meningkatkan Kompetensi Guru Dalam Membuat Karya Tulis Ilmiah di SMA Negeri 1 Tondano - Mesra, Romi; Anton, Erning Ertami; Monica, Waode Santa; Iskandar, Andi Cempana Sari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The reality at SMA Negeri 1 Tondano shows that there are still many TEACHERS who don't even know what the Mendeley or Turnitin applications are, even though as a teacher they also have to be involved in the world of literacy, especially regarding scientific publications which are also needed for promotion. The activity method that will be carried out in the Community Partnership Program (PKM) is practicum and direct demonstrations using Mendeley and Turnitin applications. The results of the service show that for the assessment tool there is an increase in data interpretation by 60.9%. This activity must be carried out every year to facilitate the creation of the right tools for teachers to assess their students, so that they continue to increase the professionalism of teachers in developing learning assessments. At the end of this training activity, participants gave positive feedback on the activity with a data interpretation of 69.6%.